Bilateral proptosis caused by orbital myositis: a case report - Aydın, Kürşad; Narin, Nazmi; Erkılıç, Kuddusi; Kurtoğlu, Selim; Hallaç, İ. Kurtuluş; Poyrazoğlu, M. Hakan (The Turkish Journal of Pediatrics, 1998)
Proptosis, unilateral or bilateral, is a frequent indication for medical evaluation and orbital computed tomography. The most common cause of proptosis in adults and children is inflammatory disorders. Orbital myositis is a subgroup of the orbital pseudotumor syndrome in which one or more of the extraocular muscles are primarily infiltrated by an inflammatory process. Computed tomography and ultrasonography showed enlargement of one or more extraocular muscles in orbital myositis.In our case, we observed clinically and by orbital computed tomography, evidence of isolated bilateral extraocular muscle swelling after upper respiratory tract infection. Proptosis and other findings were spontaneously and completely resolved after twenty days. Because proptosis caused by orbital myositis is extremely rare in children and there is limited information in the literature, this case was reported.
Keywords: proptosis; orbital myositis; childhood